Ci Opak, Jis Opak (No Canoe, No Firewood): An Economic Dimension of the Asmat Canoe - Otenieli Daeli, Onesius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
Ci is an integral part of daily life for the people of Asmat region, for geographically it is located in the lowlands and in the middle of the very broad swamp area in Papua, Indonesia. Since the rivers separate as well as connect one place from another, having a ci becomes a habitus of Asmat people. Ci means a canoe in the Asmat language. Ci is a very important cultural material to meet the needs of daily life, both personal and communal. One of the very basic Asmat expression is “Ci opak, jis opak” (no canoe, no firewood). This means that a family cannot live without a canoe because the most simple things like firewood for cooking are not available. Therefore, ci is fundamental in the life of Asmat people. Unfortunately, ci tends to be shifted or even replaced by motorised transport, while the Asmat people themselves give less attention to preserve it. As a result, they become powerless and are often described like a man who “cemen opak” (does not have a penis) or who is impotent that he is marginalised in the various fields of life.